Propuestas en el plan de desarrollo del Gobierno Autónomo Descentralizado Municipal del cantón Chone y su incidencia en el desarrollo económico - Menéndez Andrade, Jonathan Mauricio (2024)
This curricular integration work aims to analyze the Chone GAD Development Plan 2019-2023 and its impact on the productive growth of the canton, for the improvement of the quality of life of its inhabitants. To obtain it, several research methods were used, such as inductive, deductive and analytical, which allows understanding the variables from different perspectives, in addition, data collection techniques were applied through the interview and the survey that allowed obtaining information from those involved with different perspectives, as well as the types of bibliographic and field research were used. The results obtained show that the economic proposals of the PDOT described by the GAD authorities in Chone canton are focused on the livestock sectors, where genetic improvement programs for livestock have been planned through technical processes, as well as working in agriculture with several projects such as the planting of cocoa and other crops, each of these initiatives are executed through participatory budgets where all relevant unions are involved, also the incidence of these proposals shows various shortcomings in relation to the quality of life, because most people are unaware of this plan or even many who know about it have not noticed improvements in their economic situation because the activities they undertake have not been enhanced or the development of the canton is not strengthened with the execution of the plan.